2017
DOI: 10.1051/0004-6361/201628852
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of seven binary and higher-order multiple OB systems

Abstract: Analyses of multi-epoch, high-resolution (R ∼ 50000) optical spectra of seven early-type systems provided various important new insights with respect to their multiplicity. For HD 93146 A, which was hitherto assumed to be SB1, lines of a secondary component could be discerned. HD 123056 turns out to be a multiple system consisting of a high-mass component A (≈ O8.5) displaying a broad He ii 5411 Å feature with variable radial velocity, and of an inner pair B (≈ B0) with double He i lines. The binary HD 164816 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 68 publications
(118 reference statements)
2
18
0
Order By: Relevance
“…The one-sector TESS data set shows stochastic low frequency variability, and the dominant frequency satisfies our significance criterion, ν = 0.4753(7) d −1 . This approximately corresponds to the short-period found by Mayer et al (2017) but from the light curve it is unclear whether this dominant periodicity is due to binarity. HD 76556 (O6 IV(n)((f))p, Sota et al 2014) is a long-period double-lined spectroscopic binary (Chini et al 2012).…”
Section: Appendix B5: Binariessupporting
confidence: 60%
See 1 more Smart Citation
“…The one-sector TESS data set shows stochastic low frequency variability, and the dominant frequency satisfies our significance criterion, ν = 0.4753(7) d −1 . This approximately corresponds to the short-period found by Mayer et al (2017) but from the light curve it is unclear whether this dominant periodicity is due to binarity. HD 76556 (O6 IV(n)((f))p, Sota et al 2014) is a long-period double-lined spectroscopic binary (Chini et al 2012).…”
Section: Appendix B5: Binariessupporting
confidence: 60%
“…HD 123056 (O9.5 IV(n), Sota et al 2014) is a multiple system with three confirmed components, a high-mass O star orbiting in long period (∼ 1314 d) around a short-period inner pair (< 2 d) of early B stars (Mayer et al 2017). It is found to be SB1 in the IACOB/OWN spectroscopy.…”
Section: Appendix B5: Binariesmentioning
confidence: 99%
“…Until very recently, observations of high-mass binaries have commonly revealed systems with nearly equal masses (e.g. Pinsonneault & Stanek 2006;Mayer et al 2017).…”
Section: High-mass Binaries (Primary Star Mass > 5 M⊙)mentioning
confidence: 99%
“…We searched for low-mass companions in OB star binaries (Moritani et al 2018). The analysis of the 10 target stars is still ongoing, among which HD 164438 is reported to have an intermediate-mass star with the mass ratio of q = M 2 /M 1 = 0.1 -0.2 (Mayer et al 2017), where M 1 and M 2 is the initial mass of a primary and secondary, respectively. Although we have not yet established the population of binary systems in the solar vicinity, we can expect some fraction of stars that are metal-rich counterparts of the first-generation massive binaries.…”
Section: Discussionmentioning
confidence: 99%